Lập luận xấp xỉ với giá trị của biến ngôn ngữ - Sơn, TRần Thái (Journal of Computer Science and Cybernetics, 2016)
In this paper, we introduce 2 new methods of Approximate Reasoning with Values of Linguistic Variable. These methods are based on theory of Hedges Albebras. The advantage of this method included in referencing directly on values of Linguistic Variable, not using membership functions. Therfore, these methods are simple and efficient in compare with exiting methods.